The Sandblaster Software-Defined Radio Platform for Mobile 4G Wireless Communications - V. Surducan; M. Moudgill; G. Nacer; E. Surducan; P. Balzola; J. Glossner; S. Stanley; Meng Yu; D. Iancu (International Journal of Digital Multimedia Broadcasting)
We present a tier 2 Software Defined-Radio platform (SDR), built around the latest Sandbridge Technologies' multithreaded Digital Signal Processor (DSP) SB3500, along with the description of major design steps taken to ensure the best radio link and computational performance. This SDR platform is capable of executing 4G wireless communication standards such as WiMAX Wave 2, WLAN 802.11 g, and LTE. Performance results for WiMAX are presented in the conclusion section.